A teia e o labirinto - Antônio Celso Ribeiro (2016)
This thesis deals about compositional processes (creation and artistic insights), the quest for authorship (in the point of view of Analysis of Discourse - dialogism by Mikhail Bakhtin) and the presence of extramusical objects (landscapes, poetry, painting etc) as the starting point for a musical composition. In this project, I submit that extramusical elements do not act merely as a source of inspiration, but they lead all musical process with or without the interference of the composer. To support this view, I'll be bringing the concepts of instability, complexity and intersubjectivity as well the system thinking and new-paradigmatic science. These concepts move from either Taoism or Physics. Since the creational processes works in subconscious levels, I suggest the concept of caliginous zone locus where musical compositions are born (uniúsque creatione). My own compositions discussed in this thesis, particularly the one inspired by a Iranian ceramic plate dated from 1210, corroborate this hypothesis resulted from reflections that have pursued me in my experiences as author/creator.